2015
DOI: 10.1111/acem.12712
|View full text |Cite
|
Sign up to set email alerts
|

The Emergency Medicine Debate on tPA for Stroke: What Is Best for Our Patients? Efficacy in the First Three Hours

Abstract: care for our AIS patients. 22 Despite the potential for policy change, we hope that the emergency medicine community will continue to provide timely, outstanding treatment to AIS patients, including administration of tPA to those eligible. Emergency physicians are a critical part of stroke systems of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the modern reperfusion era, AIS treatment with tissue plasminogen activator (alteplase) within the first 3 hours of symptom onset, derived from the original National Institute of Neurological Disorders and Stroke alteplase trial 34 and trialist collaborative, 35 is the current standard of care 5 and has been approved by the US Food and Drug Administration since 1996. 36 Earlier administration correlates with a higher treatment effect. Alteplase also has become a standard of care for select patients within a 4.5-hour window of LKN.…”
Section: Drug/device: Ais Treatmentmentioning
confidence: 99%
“…In the modern reperfusion era, AIS treatment with tissue plasminogen activator (alteplase) within the first 3 hours of symptom onset, derived from the original National Institute of Neurological Disorders and Stroke alteplase trial 34 and trialist collaborative, 35 is the current standard of care 5 and has been approved by the US Food and Drug Administration since 1996. 36 Earlier administration correlates with a higher treatment effect. Alteplase also has become a standard of care for select patients within a 4.5-hour window of LKN.…”
Section: Drug/device: Ais Treatmentmentioning
confidence: 99%
“…Tissue plasminogen activator (tPA), an extracellular serine protease, is abundantly expressed in the nervous system. tPA catalyzes the conversion of plasminogen to plasmin and regulates the fibrinolysis [3,4], thus having been used to treat embolic or thrombotic stroke in the clinic [5,6]. Interestingly, it has been shown that the expression of tPA is changed after peripheral nerve injury [2], and tPA is likely to be implicated in peripheral nerve regeneration [7][8][9].…”
Section: Introductionmentioning
confidence: 99%